STRATEGIES OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FORMING STUDENTS' SPIRITUAL MORALS IN PRIVATE ELEMENTARY SCHOOL (MIS) AISYIYAH NORTH SUMATERA REGION - Azzahrah, Fathimah; Tanjung, Ellisa Fitri (FORUM PAEDAGOGIK, 2025)
Teachers have an important role as educators and mentors for students and are entrusted with the responsibility to educate them. Therefore, teachers need to have effective strategies to convey knowledge and guidance so that the learning process can be more easily understood by students. In the context of Islamic Religious Education in schools, the material presented includes the Qur'an, creed, worship, jurisprudence, and Islamic culture. This material is expected to provide students with an understanding of religion that is beneficial for their lives. Therefore, in addition to providing knowledge, teachers are also responsible for guiding students to be able to practice the teachings contained in the material. This is in line with the main objective of religious learning, namely to ensure that students can apply it in their daily lives. The focus of this study is the strategies used by Islamic Religious Education teachers in shaping students' spiritual morals at the Private Elementary Madrasah (MIS) 'Aisyiyah in the North Sumatra region, including the results of the guidance provided and the educational factors that influence these strategies. This study is descriptive qualitative, with data collected through interviews, observations, and other educational methods